Mobile RNAs and proteins: impacts on plant growth and productivity - Kondhare, Kirtikumar R.; Bhide, Amey J.; Banerjee, Anjan K. (Journal of Experimental Botany, 2025)
Short- and long-distance mobile signals (mobile RNAs and proteins) are integral parts of the local and systemic communications that coordinate various physiological processes at the whole-plant level and have far-reaching impacts on plant productivity. In this review, we aim to provide a comprehensive description of the integral roles of these mobile signals in controlling phenotypic traits and plant productivity. We describe how key mobile RNAs (mRNAs, small RNAs, and long non-coding RNAs) and proteins (including RNA-binding proteins) function as vital regulators of multi-faceted aspects of phenotypic traits that ultimately govern plant productivity, such as the formation of the shoot apical meristem, leaf morphology, root architecture, flowering, ripening of fleshy fruits, tuberization, crop yield, and abiotic stress responses. We also describe recent advances in the study of macromolecular transport mechanisms, such as cyclophilin-mediated transport and extracellular vesicle-based signal delivery, as well as the identification of novel signature motifs on mobile RNAs. In addition, we consider the discovery of new mobile signals and highlight how these signals can potentially be explored with advanced biotechnological interventions, virus-induced flowering, genome-editing tools, and emerging breeding approaches (e.g. the xenia-based mobile RNA delivery system for fleshy fruits) with the aim of designing strategies for enhancing valuable phenotypic traits and improving plant productivity. Mobile RNAs and proteins act as key regulators of shoot apical meristem development, leaf morphology, root architecture, flowering, fleshy fruit ripening, tuberization, yield, and responses to abiotic stresses in plants.
Keywords: Long non-coding RNA; mobile protein; mobile RNA; plant productivity; RNA-binding protein; small RNA